Hz. Muaviye’nin rivayetleri - Çakır, Durmuş Ali (My University, 2006)
TEZ ÖZETİ HZ MUAVİYE NİN RİVAYETLERİ - DURMUŞ ALİ ÇAKIR “Hz. Muâviye’nin Rivayetleri” adını taşıyan çalışma giriş ve iki ana bölümden oluşmaktadır.girişte araştırmanın amacı, önemi, planı ve metodu ortaya konulmuştur. Birinci bölümde Hz. Muâviye’nin Müslüman olmadan ve Müslüman olduktan sonraki hayatı hakkında bilgi verilmiştir. Muâviye hakkında aktarılan bilgiler objektif olmayıp tarihi gerçeklere de uymamaktadır. İkinci bölümde ise Muâviye’nin peygamberimizden yaptığı rivayetler Kütübü Tis’a çerçevesinde Ahmed b. Hanbel’in Müsned’i esas alınarak incelenmiştir. Bu incelemede 114 hadis ele alınmıştır. Bu hadislerde bulunan şahısların tam isimleri, vefat tarihleri ve güvenilirlik durumları kaynaklardan aktarılmıştır. Bu şahıslardan; 188’nin güvenilir, 8’nin güvenilirliğinin zayıf, 23’nün güvenilirliği ihtilaflıdır, 5’i hakkında ise herhangi bir bilgi bulunamamıştır. Hadislerin daha iyi anlaşılabilmesi için, metinlerindeki farklılıklara ayrıca işaret edilmeye çalışılmıştır. Rivayetlerin 39 farklı alanda olduğu ve her bir hadisin başlı başına ayrı bir çalışma konusu olabileceği görülmüştür. Ayrıca Muâviye ’den fazla rivayette bulunan şahıslar hakkında kısaca bilgi verilmiştir. Çalışma genel bir değerlendirme niteliğindeki sonuç bölümü ile tamamlanmıştır.

OF THE THESIS TRADITIONS OF MUAVIYE - DURMUŞ ALİ ÇAKIR The work named “Hz. Muâviye’nin Rivayetleri” (“Traditions of Muâviye”) composes of an introduction two main chapters. The researcher’s purpose, importance, plan and method is displayed in the introduction. In the first chapter, information is given about the life of Muâviye before and after he became Muslim. The information conveyed about Muâviye are not objective and do not comply with historical facts. As for in the second Chapter the traditions on our prophet made by Muâviye were investigated, based on the Müsned by Ahmed b. Hanbel, in the frame of the Kütübü Tis’a (nine hadith books). 114 Hadith are discussed in this study. The full names, dates of decease and statuses of reliability of the persons found in these hadiths were conveyed from the sources. 188 of these persons mentioned herein have been found as reliable, 8 were found as infirm and the reliability for 23 of these persons is in contradiction while no information was found on 5 persons mentioned in the writ. Effort was given to point at the differences in the texts in order to make the Hadiths more comprehensible. It was observed that the traditions were made in 39 different fields and that every single hadith would constitute a study subject by itself. In addition, brief information is given on persons who displayed more traditions than Muâviye. The work was completed with the conclusion chapter having the nature of a general assessment.
Keywords: Hadis; İslam Dini